Inflated numbers of authors over time have not been just due to increasing research complexity - Papatheodorou, Stefania; Trikalinos, Thomas A.; Ioannidis, John P. A. (My University, 2008)
Objective: To examine trends in and determinants of the number of authors in clinical studies. Study Design and Setting: We analyzed determinants of the number of authors in 633 articles of randomized trials and 313 articles of nonrandomized studies included in large meta-analyses (seven and six topics, respectively). Analyses were adjusted for topic. We also evaluated 310 randomly sampled case reports that had an abstract and described a single case. Results: After adjusting for topic and other determinants, for both randomized trials and nonrandomized studies, the number of authors increased by 0.8 per decade (P < 0.001). Topic was a strong determinant of the number of authors; other independent factors included journal impact factor, multinational authorship, and (for randomized trials) article length and sample size. Trials from South Europe (+1.1 authors) and North America (+0.9) and nonrandomized studies from South Europe (+1.8) had more authors than studies from North Europe (P < 0.001). For case reports, only geographic location and article length were significantly related with author numbers. Conclusion: The number of authors in articles of randomized and nonrandomized studies has increased over time, even after adjusting for the topic, size, and visibility of a study. The academic coinage of authorship may be suffering from inflation.
Keywords: Author; Authorship; Case reports; Ethics; Nonrandomized studies; Randomized trials